Evaluasi Implementasi Kebijakan Pengendalian Mutu Dan Keamanan Pangan Segar Asal Tumbuhan Dalam Rangka Perlindungan Konsumen - Djoko Rianto Budi Hartono (IJEEM - Indonesian Journal of Environmental Education and Management, 2018)
This study aims to determine the implementation of quality control and safety policies fresh food of plant origin (FFPO) in order to protect consumers in Jakarta. The method is used in this research is policy research. Data were analyzed descriptively on the content and the context of the policy. The results showed that the quality control policy and safety of FFPO in Jakarta did not fully protect consumers as the supervision of hazardous materials still less than the maximum and city administration are still difficulties in applying strict sanctions. Therefore, the need to revise Article 25 Paragraph (1) of Jakarta Provincial Regulation No. 8 of 2004 on Quality Control and Safety of Agricultural Commodities in Jakarta with strict sanctions.